2004
DOI: 10.1111/j.1365-2990.2003.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

Frontotemporal lobar degeneration and ubiquitin immunohistochemistry

Abstract: We set out to determine the frequency of the different pathologies underlying frontotemporal degeneration (FTD) in our brain bank series, by reviewing all cases of pathologically diagnosed FTD over the last 12 years. We identified and reviewed 29 cases of FTD and classified them using the most recent consensus criteria with further histological analysis of 6 initially unclassifiable cases. Detailed histological analysis of these 6 cases revealed variable numbers of ubiquitin-positive (tau and alpha-synuclein-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(90 citation statements)
references
References 15 publications
(21 reference statements)
3
86
0
1
Order By: Relevance
“…Two of the 17 subjects had died, one with stereotypies and one without. Both had a pathologic confirmed diagnosis of FTLD with ubiquitin-only immunoreactive changes [8].…”
Section: Resultsmentioning
confidence: 99%
“…Two of the 17 subjects had died, one with stereotypies and one without. Both had a pathologic confirmed diagnosis of FTLD with ubiquitin-only immunoreactive changes [8].…”
Section: Resultsmentioning
confidence: 99%
“…Many cases of "dementia lacking distinctive histology" (Knopman et al 1990) have subsequently been shown to exhibit positive immunostaining for ubiquitin (Josephs et al 2004;Lipton et al 2004;Mackenzie et al 2006c). In our series, brain tissue was available in 13 cases.…”
Section: Neuropathologic Considerationsmentioning
confidence: 99%
“…The pathological diagnosis of AD is made according to the presence of amyloid plaques and neurofibrillary tangles (Braak and Braak, 1996). The pathological diagnoses underlying FTLD are heterogeneous, although the most common pathological subtype is frontotemporal lobar degeneration with ubiquitin-immunoreactive changes (FTLD-U) (Josephs, et al, 2004). Understanding the natural progression of these diseases will be important for the assessment of future disease modifying treatments.…”
Section: Introductionmentioning
confidence: 99%